Letters, telegrams and cards of sympathy, sent to May Duggan on the death of her husband Éamonn Duggan - Duggan, May (1936)
Following the death of her husband, the Cumann na nGaedhael politician Éamonn (Edmund) Duggan on June 6 1936 his wife received letters, telegrams and cards from friends and colleagues. Among those writing to her were Margaret Pearse, Seán McGarry, Joseph Edelstein, James Dillon, Dan Breen, Joseph Holloway, Robert Briscoe, Sean Milroy, Seán MacEntee, Eamon Price and representatives of various county and district councils and trade unions.
Also included are calling cards left by visitors to the Duggan family home following Éamonn Duggan's death. Many are annotated with personal messages of sympathy. Cards are from amongst others Ernest Blythe, Eoin MacNeill, George Gavan Duffy, Fionan Lynch, Jenny Wyse Power and Eamon de Valera.
Keywords: Duggan, Éamonn, -- 1874-1936